On-Chip Curing by Microwave for Long Term Usage of Electronic Devices in Harsh Environments. Issue 1 (December 2018) - Park, Jun-Young; Kim, Weon-Guk; Bae, Hagyoul; Jin, Ik; Kim, Da-Jin; Im, Hwon; Tcho, Il-Woong; Choi, Yang-Kyu
Abstract Microwave-induced thermal curing is demonstrated to improve the reliability and to prolong the lifetime of chips containing nanoscale electron devices. A film containing graphite powder with high microwave absorbing efficiency was fabricated at low cost. The film is flexible, bendable, foldable, and attachable to a chip. A commercial off-the-shelf chip and a representative 3-dimensional (3D) metal-oxide-semiconductor field-effect transistor (MOSFET), known as FinFET, were utilized to verify the curing behaviors of the microwave-induced heat treatment. The heat effectively cured not only total ionizing dose (TID) damage from the external environment, but also internal electrical stress such as hot-carrier injection (HCI), which are representative sources of damages in MOSFET insulators. Then, the characteristics of the pre- and post-curing electron devices are investigated using electrical measurements and numerical simulations.